A half-sandwich TaV dichlorido complex containing an O,N,O'-tridentate Schiff base ligand: synthesis, crystal structure and in vitro cytotoxicity - Trávníček, Zdeněk; Štarha, Pavel; Čajan, Michal; Dvořák, Zdeněk (Acta crystallographica. Section C, Structural chemistry, 2019)
A new electroneutral half-sandwich tantalum(V) dichlorido complex containing pentamethylcyclopentadienyl (Cp*) and the double-deprotonated version of the Schiff base 2-ethoxy-6-{(E)-[(2-hydroxyphenyl)imino]methyl}phenol (H2L) as ligands, namely cis-dichlorido(2-ethoxy-6-{(E)-[(2-oxidophenyl)imino]methyl}phenolato-κ3O,N,O')(η5-pentamethylcyclopentadienyl)tantalum(V), [Ta(C10H15)(C15H13NO3)Cl2] or [Ta(η5-Cp*)(L)Cl2], has been prepared and thoroughly characterized by elemental analysis, IR and NMR spectroscopy, mass spectrometry, density functional theory (DFT) calculations and single-crystal X-ray diffraction. The molecular structure revealed that the TaV centre is coordinated by a η5-Cp* ligand, two monodentate chlorido ligands and one O,N,O'-tridentate L2- ligand. The crystal structure is stabilized by C-H...C, C-H...Cl and C...C intermolecular interactions. Moreover, the complex shows notable in vitro cytotoxicity against the A2780 human ovarian carcinoma cell line, with IC50 = 14.4 µM, which is higher than that of the conventional platinum-based anticancer drug cisplatin (IC50 = 20.1 µM).
Keywords: krystalografie rentgenová; protinádorové látky; ligandy; Cell Line, Tumor; Models, Chemical; molekulární struktura; komplexní sloučeniny; Molecular Structure; Ligands; Density Functional Theory; Crystallography, X-Ray; half-sandwich; Coordination Complexes; teorie funkcionálu hustoty; Tantalum; lidé; cytotoxicity; Humans; Schiffovy báze; DFT; Schiff Bases; crystal structure; Schiff base; tantalum(V); nádorové buněčné linie; tantal; chemické modely; phenolate; Antineoplastic Agents